2018
DOI: 10.4103/ijpvm.ijpvm_329_15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D supplementation on weight loss, glycemic indices, and lipid profile in obese and overweight women: A clinical trial study

Abstract: Introduction:Vitamin D (vit D) deficiency has defined as a health problem worldwide. World Health Organization (WHO) has declared that obesity is an epidemic of the 21st century. Previous studies have shown that obesity may increase the risk of Vit D deficiency. Furthermore, other studies have demonstrated that vit D insufficiency was accompanied with higher risk of type 2 diabetes, cardiovascular diseases, hypertension, and obesity. The aim of this study was to survey the effect of vit D supplementation on we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 40 publications
2
25
0
2
Order By: Relevance
“…Vitamin D has previously been identified as a contributing factor during weight loss [ 23 , 24 ]. We therefore set out to determine if body weight and body composition were altered by changes in vitamin D status in aged mice.…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin D has previously been identified as a contributing factor during weight loss [ 23 , 24 ]. We therefore set out to determine if body weight and body composition were altered by changes in vitamin D status in aged mice.…”
Section: Resultsmentioning
confidence: 99%
“…Metformin is a well-known drug used in the management of obesity, for its capability in reducing body weight in obese patients [ 35 , 36 ]. In addition, vitamin D supplementation has been shown to induce a decrease in weight and body mass index (BMI), reducing the risk of developing type 2 diabetes, cardiovascular diseases, and hypertension [ 37 ]. Furthermore, it is demonstrated that obesity is associated with low levels of circulating vitamin D, and with a reduced activity of CYP450 involved in its activation [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D might have a preventive effect on adiposity but no treatment effect on overweight and obesity. [14][15][16][17][18] Therefore, our study only selected adults who had a normal weight at baseline. Our findings of the inverse associations in adults of normal weight were consistent with those of a previous study of 4659 elderly women; in that study, women with higher baseline 25(OH)D level gained less weight over 4.5 years of follow-up in a subgroup of predominately normal weight at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…13 Vitamin D may have a preventive effect on adiposity for individuals of normal weight but no treatment effect for the already overweight or obese individuals. [14][15][16][17][18] Thus, the objective of this study was to investigate the relationship of serum 25(OH) D level with weight change and the risk of weight gain among adults with normal weight at baseline who participated in the Nord-Trøndelag Health Study (HUNT) and were followed up for over 11 years.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation